The Critical Appraisal of Drug Advertisement Directly to Consumers: A Mockery of Drugs and Magic Remedy (Objectionable Advertisements) Act - Meshram, Satin Kalidas; Ambade, Vipul Namdeorao; Tumram, Nilesh Keshav; Borkar , Jaydeo Laxman (Journal of Indian Academy of Forensic Medicine, 2014)
Media has a profound effect over masses to shape and mould the ideas regarding any product.  Thus it is an essential tool for mass awakening and welfare of the public at a large. But regarding drugs  this tool of advertisement should be used very meticulously. If pharmaceutical companies are allowed to  advertise the drugs, then it leads to increase in self medication and the society has to face the menace of  adverse effects for long lasting time. Despite the existing legislations banning the advertisement of drugs  in certain diseased conditions, lucrative advertisements of drugs and medical remedies are freely flowing  in the Indian mass media nowadays. These advertisements allure the vulnerable consumers thus  increasing the threat of self medication in the society.  Through this article it is tried to critically appraise the advantages, disadvantages and remedies  regarding direct to consumer drugs advertisement.
Keywords: Drug Advertisement; Drug and Magic Remedy Act; Critical Appraisal; OTC; DTCA